Maize (Zea mays L.) Grain Yield Response to Methods of Nitrogen Fertilization. Issue 21 (30th November 2019) - Oyebiyi, Fikayo B.; Aula, Lawrence; Omara, Peter; Nambi, Eva; Dhillon, Jagmandeep S.; Raun, William R.
ABSTRACT: In the developing world, fertilizer application is commonly achieved by broadcasting nutrients to the soil surface without incorporation. A commonly used nitrogen (N) source is urea and if not incorporated, can sustain N losses via ammonia volatilization and lower crop yields. This study evaluated the effect of planting, N rate and application methods on maize ( Zea mays L.) grain yield. An experiment with a randomized complete block design (nine treatments and three replications) was established in 2013 and 2018 in Oklahoma. The planting methods included; farmer practice (FP), Oklahoma State University hand planter (OSU-HP), and John Deere (JD) mechanical planter. Side-dress N application methods included; dribble surface band (DSB), broadcast (BR), and OSU-HP. Nitrogen was applied at the rate of 30 and 60 kg ha −1 as urea and UAN at V8 growth stage. On average, planting and applying N at 60 kg ha −1 using OSU-HP resulted in the highest yield (11.4 Mg ha −1 ). This exceeded check plot yield (5.59 Mg ha −1 ) by 104%. Nitrogen application improved grain yield by over 57% when compared to the 0-N check (8.77 Mg ha −1 ). Mid-season N placement below the soil surface using OSU-HP makes it a suitable alternative to improve grain yield.